2020
DOI: 10.1101/2020.06.01.128504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ICOS signaling limits regulatory T cell accumulation and function in visceral adipose tissue

Abstract: A unique population of Foxp3 + regulatory T cells (T R ) resides in visceral adipose tissue (VAT) that regulates adipose inflammation and helps preserve insulin sensitivity. The costimulatory molecule ICOS is highly expressed on effector (e)T R that migrate to nonlymphoid tissues, and contributes to their maintenance and function in models of autoimmunity. In this study, we report an unexpected cell-intrinsic role for ICOS expression and downstream PI3K signaling in limiting the abundance, VAT-associated pheno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 80 publications
(174 reference statements)
0
4
0
Order By: Relevance
“…Although above, several limitations of this study should be acknowledged. First, Treg cells resident in different non‐lymphoid tissues exhibit tissue‐specific properties, while our study focused on Tregs differentiation in VAT 40 . Second, it is well‐established that a large fraction of VAT Treg cells express the IL‐33 receptor ST2 as well as KLRG1 and CCR2, especially in male mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although above, several limitations of this study should be acknowledged. First, Treg cells resident in different non‐lymphoid tissues exhibit tissue‐specific properties, while our study focused on Tregs differentiation in VAT 40 . Second, it is well‐established that a large fraction of VAT Treg cells express the IL‐33 receptor ST2 as well as KLRG1 and CCR2, especially in male mice.…”
Section: Discussionmentioning
confidence: 99%
“…First, Treg cells resident in different non-lymphoid tissues exhibit tissue-specific properties, while our study focused on Tregs differentiation in VAT. 40 Second, it is well-established that a large fraction of VAT Treg cells express the IL-33 receptor ST2 as well as KLRG1 and CCR2, especially in male mice. An additional subset of VAT Treg cells is characterized by a naive-like phenotype, expressing CD73 and TCF-1, 41 while the current study assessed Treg differentiation in VAT using CD4 + , CD25 + and FOXP3 + antibodies.…”
Section: Tgfβ Inhibitory Cytokines a Previous Study Has Demonstrated ...mentioning
confidence: 99%
“…Interestingly, they reported that insulin signaling plays a key role for the transition from CD73 hi ST2 lo Tregs into CD73 lo ST2 hi Tregs through an HIF-1α-Med23-PPARγ axis [17] . A third population of ST2 − CD73 − CXCR3 + eVAT Tregs have also been identified through additional single cell analyses, and these cells have been reported to differentiate in response to Th1-associated IFNγ production [15,42] Additionally, Mittelsteadt et al found that deletion of ICOS significantly increased Tregs in the VAT, but not in subcutaneous adipose tissue, skin, lung, or spleen, suggesting a unique role for ICOS signaling in suppressing VAT Treg expansion [43] . Mechanistically, they propose that loss of ICOS promotes accumulation of VAT Tregs through promoting CCR3 expression.…”
Section: Other Factorsmentioning
confidence: 99%
“…After being stimulated by antigens, ICOS is expressed on activated T lymphocytes to enhance the immune response of T lymphocytes to antigens (17). Loss of ICOS signaling can promote the accumulation of regulatory T cells in visceral adipose tissue (18). A previous study found a large number of ICOS expressions in atherosclerotic plaques of ApoE −/− mice, and proposed the possibility that ICOS has a protective effect on AS (19).…”
Section: Introductionmentioning
confidence: 99%